Strategi manajemen keuangan UMKM dalam meningkatkan akses pembiayaan dan keberlanjutan ekonomi di Indonesia - Zulhelmi Zulhelmi; Himmatul Khairi (JURNAL BISNIS DAN PEMBANGUNAN, 2026)
Micro, Small, and Medium Enterprises (MSMEs) constitute a fundamental pillar of Indonesia’s economic development. Despite their strategic role, limited access to external financing remains a structural constraint, often rooted in weak financial management practices. This study aimed to critically synthesize the literature on financial management strategies of MSMEs in strengthening financing access and promoting sustainable economic development in Indonesia. This study employed a narrative literature review approach by systematically analyzing 42 peer-reviewed articles published between 2015 and 2025. The articles were retrieved from major academic databases including Google Scholar, Scopus, and ScienceDirect using predefined keywords related to financial management, MSMEs, financing access, and economic sustainability. The selected studies were examined using thematic analysis to identify key patterns, dominant financial management dimensions, and their relationships with financing accessibility and long-term business sustainability. The review demonstrates that structured financial management, particularly cash flow control, standardized financial reporting, financial literacy, capital structure planning, and working capital management, significantly enhances transparency, reduces information asymmetry, and improves MSMEs’ creditworthiness. These internal capabilities increase the probability of obtaining formal financing and strengthen financial resilience. The findings further indicate that financially disciplined MSMEs exhibit higher adaptability, competitiveness, and long-term sustainability. This study contributes to the literature by providing an integrated conceptual synthesis that links financial management capability, financing accessibility, and economic sustainability within the MSME context in Indonesia. The findings also offer policy implications for strengthening MSME financial governance and improving financial inclusion strategies